2023
DOI: 10.1186/s40001-023-01061-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of feature biomarkers associated with immune cells in neonatal sepsis

Abstract: Background Neonatal sepsis (NS), a life-threatening condition, is characterized by organ dysfunction and is the most common cause of neonatal death. However, the pathogenesis of NS is unclear and the clinical inflammatory markers currently used are not ideal for diagnosis of NS. Thus, exploring the link between immune responses in NS pathogenesis, elucidating the molecular mechanisms involved, and identifying potential therapeutic targets is of great significance in clinical practice. Herein, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The expression of PROS1 shows a positive correlation with neutrophil count, activity, and oxidative burst, suggesting its potential as a therapeutic target for conditions like decompensated liver cirrhosis and sepsis [38]. PROS1 emerges as a promising targeted drug candidate for the treatment of inflammatory disorders, including spinal cord injury and ankylosing spondylitis [38]. In this study, PROS1 was found to be downregulated in the group with DFU, suggesting its potential as a protective factor against DFU.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The expression of PROS1 shows a positive correlation with neutrophil count, activity, and oxidative burst, suggesting its potential as a therapeutic target for conditions like decompensated liver cirrhosis and sepsis [38]. PROS1 emerges as a promising targeted drug candidate for the treatment of inflammatory disorders, including spinal cord injury and ankylosing spondylitis [38]. In this study, PROS1 was found to be downregulated in the group with DFU, suggesting its potential as a protective factor against DFU.…”
Section: Discussionmentioning
confidence: 49%
“…When PROS1 is deficient, there is an increase in the expression of pro-inflammatory cytokines such as TNF-α and CCL3 [37]. The expression of PROS1 shows a positive correlation with neutrophil count, activity, and oxidative burst, suggesting its potential as a therapeutic target for conditions like decompensated liver cirrhosis and sepsis [38]. PROS1 emerges as a promising targeted drug candidate for the treatment of inflammatory disorders, including spinal cord injury and ankylosing spondylitis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that NSUN7 may be associated with an excessive inflammatory response in sepsis 40 . In addition, NSUN7 has been reported to be closely associated with immune and inflammatory responses and may be a biomarker for the pathogenesis of neonatal sepsis 41 . After SARS-CoV-2 infection, some severe patients will develop sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…NSUN7 , a member of the NSUN methyltransferase family, reduces protein activity and motility of sperms and is associated with male infertility ( 45 ). A recent study has reported that NSUN7 is up-regulated in neonatal sepsis, combined with bioinformatic analyses, NSUN7 is closely related to immune and inflammatory responses, implying its potential as a biomarker for the pathogenesis of neonatal sepsis ( 46 ). Consistently, we verified NSNU7 was highly expressed in adult septic patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%